S-Transformations: A practical tool for deformation monitoring - Setan, Halim (1995)
During the process of rigorous least squares estimation (LSE) and deformation detection, it is required to transform the results (Le. coordinates and cofactor matrix) from one datum to another datum re-definition. In this paper, the application of general equation of Stransformatiors as a tool for datum re-definition in deformation monitoring is presented. In addition, two numerical examples are also included.